JRA-55C: Monthly Means and Variances ... - Japan Meteorological Agency/Japan (UCAR/NCAR - Research Data Archive, 2015)
As a subset of the Japanese 55-year Reanalysis (JRA-55) project, the Meteorological Research Institute of the Japan Meteorological Agency has conducted a global atmospheric reanalysis that assimilates only conventional surface and upper air observations, with no use of satellite observations, using the same data assimilation system as the JRA-55. The project, named the JRA-55 Conventional (JRA-55C), aims to produce a more homogeneous dataset over a long period, unaffected by changes in historical satellite observing systems. The dataset is intended to be suitable for studies of climate change or multidecadal variability. The reanalysis period of JRA-55C is from November 1972 to December 2012. The JMA recommends the use of JRA-55 to extend JRA-55C back to January 1958.The Data Support Section at NCAR has downloaded all JRA-55C data. The entire archive has been reorganized into single parameter time series, and model resolution data has been transformed to a regular Gaussian grid. The JRA-55C products are ...